Filter Size Analysis For Optimizing Cooling Temperature In Main Engine (Case Study In Training Vessel AE-028) - Sulistyono, Noor (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
The main engine is an aircraft that has a very important role on the vessel to support the operation of the vessel, so that the vessel can operate properly. To support the performance of the main engine, there are several systems in it and one of them is a fresh water cooling system. In principle, a fresh water cooling system is the surrender of heat generated by combustion of fuel in the cylinder, so that the engine temperature will be in accordance with what is desired in this study. The purpose of this research is to find out what causes the rise in temperature of the main engine. The study was conducted at Training Vessel AE-028 for 2 months, by taking data on problems that occur in the engine coolant on the main engine on the vessel. The variable is the filter on the old Sea Chest and compared with the new filter (modification). The increase in the temperature of the fresh water cooling of the Training Vessel AE-028 is influenced by the sea water discharge from the incoming sea chest that is less than optimal. With the use of a new sea chest (modified), the water flow has increased the average flow rate to 20% and the temperature of the freshwater cooler has decreased 4.6%. By modifying the sea chest filter, the temperature of the fresh water cooler has decreased by 3 ° C and the exhaust temperature at 2 ° C. The data analysis technique used in solving hypotheses is descriptive analysis. Descriptive analysis is to provide an overview of the data obtained.